ANALISIS KEMAMPUAN BERPIKIR KRITIS DALAM PEMBELAJARAN VIRUS MELALUI MODEL PROBLEM BASED LEARNING (PBL) PADA SISWA KELAS X SMA NEGERI 1 PEKALONGAN - Melan Nica Sari; Muhfahroyin; HRA Mulyani (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2026)
Critical thinking is an intellectual thinking process in which the thinker deliberately assesses the quality of decision-making when using all of these skills effectively in the right context and type. Learning Biology not only requires mastery of concepts, but also critical thinking skills needed in solving real problems. This research aims to analyze the critical thinking ability of students in learning biology on virus material through the application of the Problem Based Learning (PBL) model at SMA Negeri 1 Pekalongan. The research method used is qualitative descriptive, with the research subject of class X students of SMA Negeri 1 Pekalongan for the 2025/2026 school year. Data collection is done through observation, critical thinking ability test, interview, and documentation. Data is analyzed through the stages of data reduction, data presentation, and drawing conclusions. Research results show that the PBL model can improve the critical thinking ability of students on viral material. This can be seen from the increase in student activity in identifying problems, analyzing data, and compiling solutions based on scientific concepts. In addition, PBL is also able to grow a deeper interest in learning and a deeper understanding of concepts because learners are directly involved in the problem-solving process. Thus, learning using the PBL model is effectively applied in improving the critical thinking skills of students in biology subjects, especially in the virus material in class X of SMA Negeri 1 Pekalongan.